2015
DOI: 10.1039/c5ra17193h
|View full text |Cite
|
Sign up to set email alerts
|

Effects of monovalent ions on membrane potential and permselectivity: evaluation of fixed charge density of polymer based zirconium aluminophosphate composite membrane

Abstract: The composite of poly(vinyl chloride) (PVC) with zirconium aluminophosphate (ZrAlP) employed as additive was prepared by sol–gel method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…S1). The TGA curve shows a little weight loss of 9.92% at 92 36. ℃ confirming the presence of low water molecules in the composite material.…”
mentioning
confidence: 51%
See 2 more Smart Citations
“…S1). The TGA curve shows a little weight loss of 9.92% at 92 36. ℃ confirming the presence of low water molecules in the composite material.…”
mentioning
confidence: 51%
“…Co-ion transport could results from either diffusive (i.e., concentration driven) transport from high to low concentration, or field-driven migration of co-ions, where the relative magnitude of each form of transport is sensitive to the concentration difference and the magnitude of the applied electric field [36,56,57]. It is thus a valuable parameter to know how these specific ions influence the ion transport in composite ion-exchange membranes [58], it can be expressed as:…”
Section: Permselectivity Of the Composite Membranementioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that the separation factor of fluoride to chloride was around 0.2 while the factor of iodine to chloride could reach around 3.5 by adjusting the membrane cross-linkage. On the other hand, recent studies revealed that membrane permselectivity is influenced by co-ion and counterion spices through ion-membrane interaction which shifts the membrane surface potential. More specifically, higher counter-ion binding affinity and higher co-ion polarizability both may result in lower permselectivity …”
Section: Recovery Of Inorganic Saltmentioning
confidence: 99%
“…From eq 16, if t + m = 1 then there will be complete cation transfer, and if t + m = t + , then no transfer of cations took place through the membrane. 79,80 The membrane fixed-charge density was calculated using the following:…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%